2021
DOI: 10.1136/jnnp-2020-325838
|View full text |Cite
|
Sign up to set email alerts
|

NOTCH3 variants are more common than expected in the general population and associated with stroke and vascular dementia: an analysis of 200 000 participants

Abstract: BackgroundCysteine-altering NOTCH3 variants identical to those causing the rare monogenic form of stroke, CADASIL (cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy), have been reported more common than expected in the general population, but their clinical significance and contribution to stroke and dementia risk in the community remain unclear.MethodsCysteine-altering NOTCH3 variants were identified in UK Biobank whole-exome sequencing data (N=200 632). Frequency of s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
62
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(69 citation statements)
references
References 36 publications
5
62
2
Order By: Relevance
“…We are not aware of previous studies investigating these five genes in a population-based setting. There has however been a study of another monogenic cSVD gene, which demonstrated that ∼1:450 UKB participants carry a putative pathogenic (i.e., cysteine-altering) variant NOTCH3 19 . Among the few disease-based studies exploring rare variation in cSVD genes in apparently sporadic cases, one large study found that ∼1:70 lacunar stroke patients had a monogenic cause 13 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We are not aware of previous studies investigating these five genes in a population-based setting. There has however been a study of another monogenic cSVD gene, which demonstrated that ∼1:450 UKB participants carry a putative pathogenic (i.e., cysteine-altering) variant NOTCH3 19 . Among the few disease-based studies exploring rare variation in cSVD genes in apparently sporadic cases, one large study found that ∼1:70 lacunar stroke patients had a monogenic cause 13 .…”
Section: Discussionmentioning
confidence: 99%
“…We found no significant interactions with sex (HTRA1 p=0.41; COL4A1 p=0.14; COL4A2 p=0.49) and ethnicity (HTRA1 p=0.60; COL4A1 p=0.88; COL4A2 p=0. 19) for any gene.…”
Section: (Which Was Not Certified By Peer Review) Preprintmentioning
confidence: 99%
See 1 more Smart Citation
“…(NOTCH3) gene, which is directly responsible for one form of VaD, and Apolipoprotein E (APOE) variants (Skoog et al, 1998;Thomas et al, 2000;Cho et al, 2021). NOTCH3 is directly linked to cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy also known as CADASIL (Papakonstantinou et al, 2019).…”
Section: Smokingmentioning
confidence: 99%
“…Much work has been done on gene variants in AD, and the effects of these genes in VaD have been rendered. The leading players in VaD include a mutation in the Notch Receptor 3 (NOTCH3) gene, which is directly responsible for one form of VaD, and Apolipoprotein E (APOE) variants ( Skoog et al, 1998 ; Thomas et al, 2000 ; Cho et al, 2021 ). NOTCH3 is directly linked to cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy also known as CADASIL ( Papakonstantinou et al, 2019 ).…”
Section: Sex-specific Differences In Vadmentioning
confidence: 99%